Using prediction strategy to enhance reading comprehension skill for the 10th form students at a high school in Ninh Binh province = Sử dụng chiến lược phán đoán để nâng cao kỹ năng đọc hiểu cho học sinh lớp 10 tại một trường trung học phổ thôn - Bùi, Thị Tú Anh (2019)
This research is an investigation into the predominant problems in learning reading at a high school in Ninh Binh province and the implementation a of new reading strategy, which is prediction strategy in this case to deal with the situation. The primary purpose of the study is an attempt to examine the impact of using prediction strategy on the improvement of reading comprehension skill of the 10th form students and find out effective ways to implement prediction strategy in reading comprehension lessons.